Aspergillus fumigatus Infection in Humans With STAT3-Deficiency Is Associated With Defective Interferon-Gamma and Th17 Responses - Danion, François; Aimanianda, Vishukumar; Bayry, Jagadeesh; Duréault, Amélie; Wong, Sarah Sze Wah; Bougnoux, Marie-Elisabeth; Tcherakian, Colas; Alyanakian, Marie-Alexandra; Guegan, Hélène; Puel, Anne; Picard, Capucine; Lortholary, Olivier; et al. (Frontiers in Immunology, 2020)
In humans, loss-of-function mutation in the Signal Transducer and Activator of Transcription 3 (STAT3) gene is frequently associated with susceptibility to bacterial as well as fungal infections including aspergillosis, although its pathogenesis remains largely unknown. In the present study, we investigated the immune responses obtained after stimulation with Aspergillus fumigatus in STAT3-deficient patients. A. fumigatus conidial killing efficiencies of both monocytes and neutrophils isolated from whole blood samples of STAT3-deficient patients were not different compared to those of healthy controls. After stimulation with A. fumigatus conidia, lower concentrations of adaptive cytokines (IFN-, IL-17 and IL-22) were secreted by peripheral blood mononuclear cells from STAT3-deficient patients compared to those from healthy controls. Moreover, the frequency of IFN- and IL-17 producing CD4+ T cells was lower in STAT3-deficient patients versus healthy controls. Among the STAT3-deficient patients, those with aspergillosis showed further lower secretion of IFN-γ upon stimulation of their PBMCs with A. fumigatus conidia compared to the patients without aspergillosis. Together, our study indicated that STAT3-deficiency leads to a defective adaptive immune response against A. fumigatus infection, particularly with a lower IFN-γ and IL-17 responses in those with aspergillosis, suggesting potential therapeutic benefit of recombinant IFN-γ in STAT3-deficient patients with aspergillosis.